2020
DOI: 10.1002/art.41421
|View full text |Cite
|
Sign up to set email alerts
|

Does Pain at an Earlier Stage of Chondropathy Protect Female Mice Against Structural Progression After Surgically Induced Osteoarthritis?

Abstract: Objective Female C57BL/6 mice exhibit less severe chondropathy than male mice. This study was undertaken to test the robustness of this observation and explore underlying mechanisms. Methods Osteoarthritis was induced in male and female C57BL/6 or DBA/1 mice (n = 6–15 per group) by destabilization of the medial meniscus (DMM) or partial meniscectomy (PMX). Some mice were ovariectomized (OVX) (n = 30). In vivo repair after focal cartilage defect or joint immobilization (sciatic neurectomy) following DMM was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
(76 reference statements)
4
19
0
Order By: Relevance
“…Moreover, even NPs distribution, accumulation, degradation rates, and toxicokinetic profiles are gender-related [ 59 , 60 ]. Some studies reported that male rats and mice show a higher OA incidence and severity compared to females, both in spontaneous and surgically induced OA models [ 61 , 62 , 63 ]. Indeed, chemically induced OA female rats exhibit a greater vulnerability to chronic pain than males [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, even NPs distribution, accumulation, degradation rates, and toxicokinetic profiles are gender-related [ 59 , 60 ]. Some studies reported that male rats and mice show a higher OA incidence and severity compared to females, both in spontaneous and surgically induced OA models [ 61 , 62 , 63 ]. Indeed, chemically induced OA female rats exhibit a greater vulnerability to chronic pain than males [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DMM induced instability leads to cartilage degradation from 2 weeks post-surgery and progressively expands to subchondral bone sclerosis and osteophyte formation 63,64 . Asymmetric weight-bearing has been reported to occur from 8 65 , to 12 weeks post-surgery, which is reversed by celecoxib and morphine 63 . In a further study, mice developed secondary mechanical hypersensitivity (von Frey) from 4 weeks, maintained up to 16 weeks (Fig.…”
Section: Destabilization Of the Medial Meniscusmentioning
confidence: 99%
“…Partial MNX is achieved by unilaterally cutting the medial meniscus. In mice, this model leads to osteoarthritic changes 4 weeks post-surgery, increased mechanical sensitivity from 8 weeks post-surgery measured by von Frey filaments 78 , and altered weight-bearing from 7 weeks 65,79 . Partial MNX has been recently used in a proof of concept study where immunisation targeting NGF reduced asymmetric weight-bearing in mice 79 .…”
Section: Meniscectomy and Medial Meniscal Transectionmentioning
confidence: 99%
See 2 more Smart Citations